Mind-body therapies for pro-inflammatory cytokines in patients with depression: findings from a systematic review of randomized controlled trials - Mei, Zhengyang; Luo, Shi; Cai, Chenyi; Lam, Chifong; Wang, Tingfeng; Jia, Haichang; Chen, Longjiang; He, Ranran (Frontiers in Immunology, 2025)
ObjectiveDepression is one of the most common mental disorders and is the leading cause of disability worldwide. The objective of this systematic review was to synthesize the latest evidence from randomized controlled trials (RCTs) regarding the effectiveness of mind-body therapies (MBTs) on pro-inflammatory cytokines in patients with depression.MethodsA literature search was conducted in five electronic databases—PubMed, Embase, Web of Science, EBSCOhost, and Scopus. The quality of the included studies was evaluated using the Revised Cochrane risk-of-bias tool for randomized trials (RoB 2). A narrative synthesis of the included studies was conducted.ResultsThe 12 RCTs provided 21 pieces of evidence involving a total of 1,058 patients with depression. The risk of bias among the included studies ranged from low to high, with 4 studies assessed as low risk, 4 as some concerns, and 4 as high risk. Among the 21 pieces of evidence evaluated, 14 supported the positive impact of MBTs on pro-inflammatory cytokine levels in patients with depression.ConclusionMBTs have been widely recognized in nursing for their low risk and substantial benefits, and they hold promise as a complementary therapy to improve physiological health outcomes in patients with depression. However, the studies included commonly exhibit potential limitations in terms of intervention materials, adherence, and outcome measures. It is suggested that future research should further examine the existing evidence to strengthen the empirical foundation for incorporating MBTs into nursing care for depression.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251113095.